Influence of nettle powder addition on bread quality indicators - A. M. Saidov; Zh. E. Balguzhinova; N. D. Zhangabylova; K. S. Alseitov; K. E. Iskakov (Алматы технологиялық университетінің хабаршысы, 2022)
This article reflects the results of a study on the effect of nettle leaf powder on the physicochemical and organoleptic characteristics of wheat bread. Nettle leaves is a good source of proteins, fibers, minerals and other bioactive compounds and it could be an ideal ingredient for improving the nutritional value of bread and bakery products. Nettle leaf powder was mixed with wheat flour in different ratios: 1 %, 3 % and 5 % to prepare bread samples. The results showed a significant increase in the protein, ash and fiber content of bread. The specific volume of the bread decreased as the level of nettle leaf powder increased due to a decrease in the gluten content of the mixture and due to the interaction between dietary fiber components, water and gluten. Substitutions of 1 %, 3 % and 5 % give parameter values at least the same as the control sample and give acceptable indicators of bread quality in terms of specific volume and organoleptic properties.